2018
DOI: 10.1371/journal.ppat.1007074
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa type IV minor pilins and PilY1 regulate virulence by modulating FimS-AlgR activity

Abstract: Type IV pili are expressed by a wide range of prokaryotes, including the opportunistic pathogen Pseudomonas aeruginosa. These flexible fibres mediate twitching motility, biofilm maturation, surface adhesion, and virulence. The pilus is composed mainly of major pilin subunits while the low abundance minor pilins FimU-PilVWXE and the putative adhesin PilY1 prime pilus assembly and are proposed to form the pilus tip. The minor pilins and PilY1 are encoded in an operon that is positively regulated by the FimS-AlgR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 102 publications
4
52
0
Order By: Relevance
“…It is generally thought that a mucoid strain would produce more EPS (Marko et al, 2018), and this is in agreement with our results that the mucoid pilN mutant produced enhanced EPS compared to the wild-type strain. In addition, increased biofilm formation was observed in the pilN mutant, consistent with previous reports showing that EPS production has a positive correlation with biofilm formation in Xanthomonas species (Buttner and Bonas, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…It is generally thought that a mucoid strain would produce more EPS (Marko et al, 2018), and this is in agreement with our results that the mucoid pilN mutant produced enhanced EPS compared to the wild-type strain. In addition, increased biofilm formation was observed in the pilN mutant, consistent with previous reports showing that EPS production has a positive correlation with biofilm formation in Xanthomonas species (Buttner and Bonas, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…The major pilin and minor pilins interact. To address whether the mature forms of the major pilin PilA and minor pilins of cluster_3, i.e., pilins without the type III signal peptide, interact, we used the Bacterial Two-Hybrid (BACTH) system as previously described to detect interactions between minor and major pilins of T4aP systems and the pseudopilins of type II secretion systems (T2SS) 10,[26][27][28][29][30][31] . To this end, the T18 and T25 fragments of the adenylate cyclase were fused to the N-terminus of the full-length mature pilins.…”
Section: Resultsmentioning
confidence: 99%
“…Minor pilins encoded by fimTX‐pilVX/WX/XX/EX and a nonpilin protein encoded by pilYX are required for T4P biogenesis and therefore T4P‐mediated motility and virulence (Russell and Darzins, ; Alm et al , ; Alm and Mattick, ). Interestingly, an increasing number of studies have shown that these proteins have roles in virulence independent on functional pili (Bohn et al , ; Feinbaum et al , ; Marko et al , ). These results indicate that RpoN2‐PilRX plays an important role in pilus‐dependent or pilus‐independent biological functions by directly or indirectly regulating T4P genes in Xoo.…”
Section: Discussionmentioning
confidence: 99%